Meningkatkan Keterampilan Proses Sains Siswa MTS Negeri 1 Lubuklinggau Melalui Penggunaan LKPD Berbasis Guided Inquiry - Puspita Wahyu Irawan; Endang Lovisia; Ahmad Amin (Proceeding of Silampari Conference of Life Science and Technology, 2026)
This study aims to develop valid and effective guided inquiry-based worksheets to improve junior high school students’ science process skills. This is a research and development (R&D) study using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects were 38 students at MTs Negeri 1 Lubuklinggau. The research instruments used included validation forms for subject matter experts, media experts, and language experts, as well as an observation sheet for students’ science process skills. The results showed that the guided inquiry-based worksheets received a subject matter expert validation score of 43, a media expert validation score of 48, and a language expert validation score of 69—all falling into the “very good” category—and were therefore deemed valid and suitable for use in instruction. Furthermore, the use of guided inquiry-based worksheets was able to improve students’ science process skills in the indicators of observing, classifying, predicting, measuring, drawing conclusions, and communicating, with an average N-Gain score of 0.57, which falls into the moderate category. Thus, guided inquiry-based worksheets are effective for improving the science process skills of students at MTs Negeri 1 in Lubuklinggau.